Extracellular release of acid phosphatase from blood stream forms of Trypanosoma brucei brucei (2013)
Acid phosphatase (ACP) activity was demonstrated in blood stream form of Trypanosome brucei brucei harvested from infected Wister rats by Ion Exchange DEAE Cellulose 52 chromatography. Whole parasite extract (WPE) and Excretory Secretory Extract (ESE) were prepared and analyzed for acid phosphatase activity. A higher ACP activity (85.5 μmol/min) was recorded in WPE compared to ESE (36.8 μmol/min). ACP activity in ESE is suggestive of the presence of a cell rich enzyme. Phase separation of the extracts using the detergent Triton X-114 (TX-114), resulted in protein partitioning into aqueous and detergent phases. ACP activity was higher in the detergent phases (56.2 μmol/min and 28.8 μmol/min) of WPE and ESE respectively. ACP activity recorded in the aqueous phases of WPE and EPE was 27.8 and 7.6 μmol/min respectively. On a Size Exclusion chromatography column using Sephacryl-300, ESE emerged as five distinct protein peaks. ACP activity of the eluted fractions showed two peaks of relative molecular weights 195 and 325 KD. This study shows that T. brucei releases acid phosphatase extracellularly via a yet to be determined mechanism. Acid phosphatase activity in ESE is indicative of a soluble enzyme within the cell matrix which may also play an important role in the pathology of African Trypanosomiasis.